2016
DOI: 10.1136/bcr-2015-213249
|View full text |Cite
|
Sign up to set email alerts
|

Chronic infection of a Brindley sacral nerve root stimulator

Abstract: SUMMARYThe Finetech-Brindley sacral anterior root stimulator (SARS) is implanted for the treatment of bladder dysfunction following spinal cord injury (SCI) and has been successful in improving micturition in many patients with SCI. This case describes a 62-year-old man who presented with a chronic Staphylococcus aureus infection of a Brindley SARS 26 years after implantation following a T5 American Spinal Injury Association A spinal cord injury (T5 ASIA A SCI). He presented with chronic sacral osteomyelitis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…However, it appears all reported cases pertaining to abscess formation secondary to infected SNS implant required explantation. 9,17 There is no consensus on the antibiotic choice, method of administration, dose, and duration of administration for patients undergoing antibiotic therapy for infected SNS. General advice has been published, and cephalosporins are the most used antibiotic for infected SNS, given Staphylococcus aureus is the most common cause.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, it appears all reported cases pertaining to abscess formation secondary to infected SNS implant required explantation. 9,17 There is no consensus on the antibiotic choice, method of administration, dose, and duration of administration for patients undergoing antibiotic therapy for infected SNS. General advice has been published, and cephalosporins are the most used antibiotic for infected SNS, given Staphylococcus aureus is the most common cause.…”
Section: Discussionmentioning
confidence: 99%
“…There are no guidelines stipulating which patients should undergo a trial of conservative management versus immediate complete explant, and it seems current treatment is influenced by treating surgeon and local hospital guidelines. However, it appears all reported cases pertaining to abscess formation secondary to infected SNS implant required explantation 9,17 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A critical but poorly reported area of interest was risk and safety. A handful of studies specifically included the assessment of the risks and safety of ESCS 48,51,[63][64][65][66] or the potential use of ESCS as a home therapy. 67 Unfortunately, not one study was designed and conducted to specifically examine risk and safety of TSCS or magnetic SCS for those with SCI, nor was an article found that addressed adverse events associated with research or the use of these devices in the community setting.…”
Section: Discussionmentioning
confidence: 99%